Evaluation of the Emotional and Cognitive Regulation of Young People in a Lockdown Situation Due to the Covid-19 Pandemic - Fernández Cruz, Manuel; Álvarez Rodríguez, José; Ávalos Ruiz, Inmaculada; Cuevas López, Mercedes; de Barros Camargo, Claudia; Díaz Rosas, Francisco; González Castellón, Esther; González González, Daniel; Hernández Fernández, Antonio; Ibáñez Cubillas, Pilar; Lizarte Simón, Emilio Jesús (Frontiers in Psychology, 2020)
Background. In a situation of compulsory home isolation enacted by governments at the spreading of the Covid-19 pandemic, the emotional health and well-being of students became a key factor in the successful implementation of distance teaching methodologies in face-to-face education universities. Psychological well-being, an essential factor in preventing academic failure, has been threatened in this serious situation of unprecedented and stressful isolation. The aim of this study is to analyze the students´cognitive-emotional regulation as well as their beliefs and perceptions about the pandemic and this lockdown situation. With this extensive study we are carrying out, want to describe the extent to which the lockdown situation is a risk factor, and, in the future, make proposals for preventive and palliative actions, if necessary, to minimize this potential risk. Method. We applied the CERQ Cognitive Emotion Regulation Questionnaire by means of an online application together with a questionnaire, CC/covid-19, of objective description and subjective perception of the lockdown situation of the students, their conditions to study, general opinions about the pandemic and specific opinions about the real possibilities of implementing online education in the middle of the academic year at the university. 1910 valid responses from more than 80 universities in 13 different Spanish-speaking countries were obtained and submitted to descriptive analysis and modeling using structural equations. Results. Most of them consider that the lockdown decision is correct, that health systems are not prepared to deal with the pandemic, and that although the universities have adequate means, the teaching staff is not competent to implement online teaching methodologies. They have a good perception of the conditions of isolation however the time dovoted to studying has not increased. One of the results of our study is the students´ self-evaluation about their digital competence and their capacity to perform in online interactive communication. The cognitive strategies used by the students surveyed have allowed them coping with events arising from the pandemic, mandatory isolation and university closure, certainly adaptive and functional, while maintaining a positive perception of their new living and learning situation.